2011
DOI: 10.1371/journal.pone.0017237
|View full text |Cite
|
Sign up to set email alerts
|

Specific Oncogenic Activity of the Src-Family Tyrosine Kinase c-Yes in Colon Carcinoma Cells

Abstract: c-Yes, a member of the Src tyrosine kinase family, is found highly activated in colon carcinoma but its importance relative to c-Src has remained unclear. Here we show that, in HT29 colon carcinoma cells, silencing of c-Yes, but not of c-Src, selectively leads to an increase of cell clustering associated with a localisation of β-catenin at cell membranes and a reduction of expression of β-catenin target genes. c-Yes silencing induced an increase in apoptosis, inhibition of growth in soft-agar and in mouse xeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 25 publications
2
37
0
1
Order By: Relevance
“…Although c-Src and its closest phylogenetic relative, c-Yes, are co-expressed in this cell type, c-Src activity drives ES cell differentiation while c-Yes suppresses differentiation and drives self-renewal [16][18]. Along similar lines, RNAi-mediated knock-down of c-Yes expression in colon cancer cell lines increased apoptosis and reduced cell migration and tumor growth, while c-Src knock-down yielded a much less dramatic effect on the same phenotypes, suggestive of a dominant role for c-Yes vs. c-Src in colon cancer [19]. These differences in individual functions raise fundamental questions about what mechanisms selectively regulate specific family members, especially in cellular contexts where multiple SFKs are co-expressed.…”
Section: Introductionmentioning
confidence: 80%
“…Although c-Src and its closest phylogenetic relative, c-Yes, are co-expressed in this cell type, c-Src activity drives ES cell differentiation while c-Yes suppresses differentiation and drives self-renewal [16][18]. Along similar lines, RNAi-mediated knock-down of c-Yes expression in colon cancer cell lines increased apoptosis and reduced cell migration and tumor growth, while c-Src knock-down yielded a much less dramatic effect on the same phenotypes, suggestive of a dominant role for c-Yes vs. c-Src in colon cancer [19]. These differences in individual functions raise fundamental questions about what mechanisms selectively regulate specific family members, especially in cellular contexts where multiple SFKs are co-expressed.…”
Section: Introductionmentioning
confidence: 80%
“…Sh RNAs targeting c-Yes sequences were also previously described (24). Selection of the c-Yes silenced populations was performed with puromycin (1μg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…5 and 6. DISCUSSION c-Yes, similar to other members of the SFKs (e.g., c-Src), is a (proto)oncogene, with its expression intimately related to carcinogenesis (11,29,53,57,58). For instance, overexpression of c-Yes in human colorectal carcinoma cells promotes metastatsis (3), but recent studies have shown that it also plays critical roles in different cellular physiological function, such as growth factor activation, endocytic vesicle-mediated protein trafficking, and cell signaling (11,15,68,69).…”
Section: Knockdown Of C-yes In the Testis In Vivo Disrupts Distributimentioning
confidence: 99%
“…c-Yes (or Yes 1, Yamaguchi sarcoma viral oncogene homolog 1), a nonreceptor protein tyrosine kinase and a member of the Src family kinases (SFKs) and also a proto-oncogene whose expression is upregulated in various cancers, including melanoma (29), colon cancer (58), and brain cancer (53), is also known to be involved in regulating cell cycle and cytokinesis (28). In fact, members of the SFKs are targets of chemotherapy (1,67).…”
mentioning
confidence: 99%